The Quality of Information and Related Sources of Information as an Assumption for Effective Decision-Making Process for Tourists to Travel in the European Tourism Market - MihajloviÄ‡, Iris; ÄŒoloviÄ‡, Zorica KrÅ¾elj (Richtmann Publishing, 2012)
Assumption of effective decision-making process for tourists on a trip is based on quality information. In order to gain insight ofthe source of information about tourists' decisions related to travel and to the European tourist market, a secondary research wasconducted. Subjects-tourists, who participated in the survey, were asked to indicate which sources of information they use when makingdecisions about travel plans, by valuing different sources of information as very important to less important ones. Survey results indicatehighly prevailing sources of information such as